2012
DOI: 10.1007/s11999-011-2038-0
|View full text |Cite
|
Sign up to set email alerts
|

Endoprostheses Last Longer Than Intramedullary Devices in Proximal Femur Metastases

Abstract: Background The proximal femur is the most common site of surgery for bone metastases, and stabilization may be achieved through intramedullary fixation (IMN) or endoprosthetic reconstruction (EPR). Intramedullary devices are less expensive, less invasive, and may yield improved function over endoprostheses. However, it is unclear which, if either, has any advantages. Questions/purposes We determined whether function, complications, and survivorship differed between the two approaches. Methods We retrospectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
167
1
9

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(195 citation statements)
references
References 23 publications
18
167
1
9
Order By: Relevance
“…Not surprisingly then, nearly half of the patients in this series (10 of 21) died within 1 year of the hip reconstruction. This is comparable to the survivorship reported by Harvey et al [10], in which overall patient survival at 1 year after undergoing endoprosthetic reconstruction or intramedullary nail fixation for proximal femur metastases was 51%. Hattori et al [11] reported a 1-year survival rate of 69%, although this represents only eight patients who underwent endoprosthetic reconstruction.…”
Section: Discussionsupporting
confidence: 86%
“…Not surprisingly then, nearly half of the patients in this series (10 of 21) died within 1 year of the hip reconstruction. This is comparable to the survivorship reported by Harvey et al [10], in which overall patient survival at 1 year after undergoing endoprosthetic reconstruction or intramedullary nail fixation for proximal femur metastases was 51%. Hattori et al [11] reported a 1-year survival rate of 69%, although this represents only eight patients who underwent endoprosthetic reconstruction.…”
Section: Discussionsupporting
confidence: 86%
“…We reviewed the peer-reviewed literature from 1980 through 2011 and found 14 articles describing outcomes for IMN, PFRR, LSCH/CH, and ORIF in patients treated for femoral metastases. Notably, few studies examined proximal femur fractures specifically, and 14 of 15 studies were retrospective, citing either a retrospective cohort (Level of Evidence IV) or retrospective comparison design (Level of Evidence III) (Table 5) [2,4,5,[7][8][9][10][11][12][13][14][15][18][19][20]. A single, prospective study (Level I) was found that showed functional improvement in patients undergoing surgery for nonspinal bone metastases [17], but outcomes specific to the proximal femur were not reported.…”
Section: Discussionmentioning
confidence: 99%
“…Istnieje wiele sposobów zaopatrzenia tego typu złamania: protezoplastyka resekcyjna, repozycja złamania i stabilizacja przy pomocy gwoździowania śródszpikowego lub płyty ze śrubami stabilnymi kątowo [4][5][6][7][8][9][10][11][12][13][14][15]. Najważniejsze w leczeniu chorego ze złamaniem patologicznym kości udowej jest wczesne rozpoznanie i minimalnie inwazyjna operacja pozwalająca na wczesną bezbolesną pionizację poprawiającą jakość życia [16,17,18].…”
Section: Streszczenieunclassified
“…There is a number of surgical approaches to such trauma: resection arthroplasty or fracture reposition, intramedullary nailing fixation or plate fixation using angular stable screws [4][5][6][7][8][9][10][11][12][13][14][15]. First of all, a patient with pathological femoral shaft fracture should be early recognized and treated with a minimally invasive surgery, which facilitates early and painless rehabilitation focused on bringing patient to the erect, life-quality improving, position.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation